+0  
 
0
203
1
avatar+3417 

Help.

NotSoSmart  Oct 10, 2017
 #1
avatar+89791 
+2

-4.5x - 2y  = -12.5   (1)

3.25x - y  = -0.75    →   y =  3.25x + 0.75   (2)

 

Put (2)  into (1)

 

-4.5x - 2 (  3.25x + 0.75 )  = -12.5       simplify

 

-4.5x - 6.5x - 1.5  = -12.5

 

-11x  - 1.5  = -12.5      add 1.5 to both sides

 

-11x  = -11       divide both sides by   -11

 

x  = 1

 

And using ( 2)

 

y =  3.25 (1)  + 0.75   =   4

 

 

 

cool cool cool

CPhill  Oct 10, 2017

37 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.